Comparative characteristics of diabetes risk scores - Svetlana Vladimirovna Mustafina; Galina Il'inichna Simonova; Oksana Dmitrievna Rymar (Сахарный диабет)
The worldwide prevalence of diabetes among adults (aged 20?79 years) was 8.35% in 2013, and this is expected to increase by 55% (592 million adults) by 2035. To avoid the increase in the prevalence of diabetes, primary prevention and early diagnosis of prediabetes are required. It is important to identify individuals at a high risk of hyperglycaemia using inexpensive and available methods. At present, risk score is an alternative to identify the risk of developing diabetes. There are approximately 10 types of risk scores in the world, and further research for the development and adaptation of risk scores for various populations are being conducted. The use of risk score methods for prediction allows the setting of the level of total risk, identification of high-risk patients and prescription of necessary preventive measures. Actual validation of existing diabetes risk score for the Russian population is being conducted. Assessment of the risk of diabetes is simple, fast, inexpensive, non-invasive and reliable.